2013
DOI: 10.7895/ijadr.v1i1.40
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants for alcohol consumption and heavy episodic drinking in a Ugandan student population

Abstract: Aims: To examine whether the socio-economic determinants of alcohol use found in high-income university student settings are also true of Uganda. Results:Multivariate logistic regression showed the following socio-economic determinants to be positively associated with alcohol consumption: having attended boarding school (for males only); being Catholic; religion not playing a big role while growing up; head of household having had secondary education or higher (for females only); being a student of developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Even though, Ugandan universities have a zero tolerance policy against drinking and no alcohol is allowed on campuses, students still continue to drink [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Even though, Ugandan universities have a zero tolerance policy against drinking and no alcohol is allowed on campuses, students still continue to drink [21]. …”
Section: Introductionmentioning
confidence: 99%
“…ese findings are not surprising, as several similar results show that family religiosity is protective of alcohol consumption. For instance, Stafström and Agardh [8] found that family religiosity significantly predicted alcohol consumption among students. Furthermore, in their study to determine religion and religiosity as predictors of alcohol use among adults at a fishing site in Uganda, Tumwesigye et al [28] found that people reporting low religiosity were five times more likely to have consumed alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the patterns of alcohol consumption among the youths in Uganda show signs of family influence [5]. e family, as part of the social apparatus, defines alcohol consumption among Uganda's youthful populations [6][7][8]. Despite these sources underpinning family dynamics as controlling youth drinking in Uganda, and to the best of our knowledge, no single study has set to investigate family influences on alcohol consumption among the youth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda, the relationship between alcohol use and risky sexual behaviour is complex, and it may be influenced by a combination of social, physiological, and individual personality traits (Choudhry, Agardh, Stafström & Östergren, 2014). In another study, Stafström and Agardh (2012) suggest that alcohol consumption and monthly heavy episodic drinking (HED) among students in Uganda are associated with socioeconomic background factors, but with different patterns for young men and women. Similarly, Ramsoomar and Morojele (2012) report that, although South Africa has made significant strides in alcohol control and prevention of alcohol-related harm over the past decade, early alcohol initiation remains a concern and binge drinking is increasing, especially among females.…”
Section: Background and Literature Developmentmentioning
confidence: 99%